Balancing the perceptions of NK modelling with critical insights - Richard J. Arend (Journal of Innovation and Entrepreneurship, 2022)
NK models are agent-based simulations of market evolution generated through new entry and firm innovation, and are often focused on better understanding complex interdependencies in organizational phenomena. We provide a counterpoint to the mostly optimistic descriptions of the advantages and of the requirements for these fitness-landscape-based analyses. We do so by offering a comprehensive list of limitations of that modelling technique as well as a critical analysis of two recent applications of the NK model - one of a theory-testing application and one of a theory-building application. Our analysis reveals that when care is not taken to capture the essential parts of a phenomenon, the NK approach may be unnecessary at best, and misleading at worst. We discuss the implications of these analyses and update past suggestions for future uses of NK simulations in organizational research.
Keywords: C53; C61; C63; C73; D02; D21; 650; NK models; Organizational science; Simulations; Theory building; Theory testing